The Influence Of Work Engagement, Organizational Culture, Workload And Work Stress On The Performance Of Implementing Employees In The Kebun Area Of Serdang District - Zul Ahmad Lubis; Yusniar Lubis; Ihsan Efendi (Jurnal Bisnis dan Manajemen, 2024)
The cause of a company's declining income is close to employee performance, which is not optimal. So, an in-depth analysis is needed to see whether there are various causal factors. Therefore, this research wants to test whether work engagement, organizational culture, workload, and work stress influence employee performance. This research was conducted in the Gardens of Serdang District. The data collection method uses quantitative description. The research results show that work engagement has a positive and significant effect on employee performance with a significance level of 0.001 0.05, organizational culture has a positive and significant effect on employee performance with a significance level of 0.000 0.05, workload has a positive and significant effect on employee performance with a level of significance 0.038 0.05, Job stress has a positive and significant effect on employee performance with a significance level of 0.000 0.05, and simultaneously work engagement, organizational culture, workload and work stress have a significant effect on employee performance with a significance level of 0.000 0 .05. This research only focuses on four research variables, so other variables can still influence employee performance This research is fundamental because it will provide new knowledge that several things are important in improving employee performance. So it is concluded that all research variables have a positive and significant effect on employee performance.